European championship in football in Poland and the increase in foreign tourist arrivals - Jozef Bergier; Malgorzata Wasilewska; Michal Bergier (UTMS Journal of Economics, 2018)
World-class and prestigious sporting events, especially in football, draw many international visitors. One of such events was the European Football Championship held in Poland in 2012. The number of foreign tourists arriving in 2012, compared to the year 2011, showed a significant increase in visits by 1,5 million, including 650 thousand coming exclusively for the occasion to watch the European Championships in 2012. This dynamic growth of arrivals continued in the years 2012-2015 and increased by more than 3 million persons when compared to the figures recorded in the year 2011. The dynamics of the provided accommodation and the number of one-day stays in Poland was also visible. What is more, the average expenditure of foreign tourists per person reached a record high in the year 2012 and amounted to USD 462. Also, the amount of money spent per day increased in the year 2012 by USD 82 and, in successive years, was even higher - USD 101 in the year 2013 and USD 95 in 2014. The presented data show that the organisation of European Championship in football in Poland in 2012 was an excellent opportunity to develop the Polish economy. Accordingly, it might be said that top-level sports competitions are also a chance to meet football fans from many different countries as well as start new economic endeavours.
Keywords: Z32; 330; sports events; tourism; economic growth